Cortical phase changes in Alzheimer's disease at 7T MRI: A novel imaging marker. Issue 1 (28th May 2013) - van Rooden, Sanneke; Versluis, Maarten J.; Liem, Michael K.; Milles, Julien; Maier, Andrea B.; Oleksik, Ania M.; Webb, Andrew G.; van Buchem, Mark A.; van der Grond, Jeroen
Abstract: Background: Postmortem studies have indicated the potential of high‐field magnetic resonance imaging (MRI) to visualize amyloid depositions in the cerebral cortex. The aim of this study is to test this hypothesis in patients with Alzheimer's disease (AD). Methods: T2*‐weighted MRI was performed in 16 AD patients and 15 control subjects. All magnetic resonance images were scored qualitatively by visual assessment, and quantitatively by measuring phase shifts in the cortical gray matter and hippocampus. Statistical analysis was performed to assess differences between groups. Results: Patients with AD demonstrated an increased phase shift in the cortex in the temporoparietal, frontal, and parietal regions ( P < .005), and this was associated with individual Mini‐Mental State Examination scores ( r  = −0.54, P < .05). Conclusion: Increased cortical phase shift in AD patients demonstrated on 7‐tesla T2*‐weighted MRI is a potential new biomarker for AD, which may reflect amyloid pathology in the early stages.